Targeted high-throughput sequencing of candidate genes for chronic obstructive pulmonary disease. Issue 1 (December 2016) - Matsson, Hans; Söderhäll, Cilla; Einarsdottir, Elisabet; Lamontagne, Maxime; Gudmundsson, Sanna; Backman, Helena; Lindberg, Anne; Rönmark, Eva; Kere, Juha; Sin, Don; Postma, Dirkje; Bossé, Yohan; et al.
Abstract Background Reduced lung function in patients with chronic obstructive pulmonary disease (COPD) is likely due to both environmental and genetic factors. We report here a targeted high-throughput DNA sequencing approach to identify new and previously known genetic variants in a set of candidate genes for COPD. Methods Exons in 22 genes implicated in lung development as well as 61 genes and 10 genomic regions previously associated with COPD were sequenced using individual DNA samples from 68 cases with moderate or severe COPD and 66 controls matched for age, gender and smoking. Cases and controls were selected from the Obstructive Lung Disease in Northern Sweden (OLIN) studies. Results In total, 37 genetic variants showed association with COPD (p < 0.05, uncorrected). Several variants previously discovered to be associated with COPD from genetic genome-wide analysis studies were replicated using our sample. Two high-risk variants were followed-up for functional characterization in a large eQTL mapping study of 1, 111 human lung specimens. The C allele of a synonymous variant, rs8040868, predicting a p.(S45=) in the gene for cholinergic receptor nicotinic alpha 3 (CHRNA3 ) was associated with COPD (p = 8.8 x 10−3 ). This association remained (p = 0.003 and OR = 1.4, 95 % CI 1.1-1.7) when analysing all available cases and controls in OLIN (n = 1, 534). The rs8040868 variant is in linkage disequilibrium with rs16969968 previously associated with COPD and altered expression of theCHRNA5 gene. A follow-up analysis for detection of expression quantitative trait loci revealed that rs8040868-C was found to be significantly associated with a decreased expression of the nearby gene cholinergic receptor, nicotinic, alpha 5 (CHRNA5 ) in lung tissue. Conclusion Our data replicate previous result suggestingCHRNA5 as a candidate gene for COPD and rs8040868 as a risk variant for the development of COPD in the Swedish population.